Anus : surgical treatment and pathology - Windsor, Alastair; Cohen, Richard (Springer London, 2014)
Anus: Treatment and Pathology is the perfect guide for the diagnosis and management of patients with anal canal and pelvic floor disorders. Using annotated diagrams matched to cross-sectional radiology with ultrasound and MRI, this book will not only give the reader a thorough understanding of normal anal canal and pelvic floor anatomy, but will also take the reader through the common benign and malignant conditions which affect the anal canal and pelvis describing in detail their pathophysiology, investigation and management.   Anus: Treatment and Pathology is aimed at practicing general surgeons, colorectal surgeons and surgical trainees, which can be used either as a practical reference guide for day to day colorectal surgical practice or for in depth text based learning.